2020
DOI: 10.1080/14756366.2020.1825407
|View full text |Cite
|
Sign up to set email alerts
|

Structure-activity relationship of 7-aryl-2-anilino-pyrrolopyrimidines as Mer and Axl tyrosine kinase inhibitors

Abstract: The TAM (Axl, Mer, and Tyro3) family is implicated in the survival and chemoresistance of tumours and has emerged as a potential therapeutic target. A novel series of 7-aryl-2-anilino-pyrrolopyrimidines were identified as potent Axl/Mer tyrosine kinase inhibitors without significant inhibition of Tyro3. A representative compound 27 exhibited IC 50 values of 2 nM and 16 nM for Mer and Axl, respectively, and considerable inhibition for Mer phosphorylation in cells. Docking studies suggested that the formation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…In this study, the AXL receptor is used as a therapeutic target for the development of a drug against COVID-19. The main ligand reported to bind to AXL is growth-arrest-specific 6 (GAS6) (15); this interaction has been associated with angiogenesis, cancer, metastasis, thromboembolism, and diseases of the immune and cardiovascular system (15,16). The expression of AXL is associated with drug resistance and diminished long-term survival in a wide range of malignancies (17).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the AXL receptor is used as a therapeutic target for the development of a drug against COVID-19. The main ligand reported to bind to AXL is growth-arrest-specific 6 (GAS6) (15); this interaction has been associated with angiogenesis, cancer, metastasis, thromboembolism, and diseases of the immune and cardiovascular system (15,16). The expression of AXL is associated with drug resistance and diminished long-term survival in a wide range of malignancies (17).…”
Section: Introductionmentioning
confidence: 99%
“…Aryl-substituted pyrrolopyrimidines showed potent inhibition of the membrane bound epidermal growth factor receptor tyrosine kinase (EGFR) and angiogenic inhibitors against human vascular endothelial growth factor receptor-2 (VEGFR-2) that represent important targets in cancer therapy [17][18][19][20][21][22][23][24]. Over the past years, some pyrrolo [2,3-d]pyrimidine derivatives were identified as inhibitors of Mer receptor and Src non-receptor tyrosine kinases, isoform of protein kinase B (Akt), mitotic checkpoint kinase (Mps1), Janus kinase 2 (JAK2), and phosphoinositide 3 kinase (PI3K) with promising anticancer activity [25][26][27][28][29][30][31][32][33]. Design strategy in development of purine derivatives as cytostatic agents for kinase inhibition revealed that introduction of cyclic amines improved the activity by forming an additional hydrogen bond to kinase hinge [9,34,35].…”
Section: Introductionmentioning
confidence: 99%